Line follower robot with solar application - Mohd Firdaus, Mohd Yasin (2010)
The objectives of this thesis are to construct a line follower robot where it use energy from sun and controlled using solar charger, goes to battery. This robot is dynamic and durable where is modeling using three tires, one for in front and two at the back for free to move. Before building this solar robot several studies have been made and were divided into several stages. This Line-Following robot it follows the path of the white line in a suitable ground, it will be moved automatically forwards, backwards, left and right free from the black lined path by programming. Robot is operated using two DC Motor Planetary toothed wheels on left and right sides. Forward and backward movement, or left and right side motors are controlled by two motor driver circuits. The batteries can be charged by dc supply from an external source or by DC supply from a solar panel